FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN USAHA TERNAK AYAM BROILER DI KABUPATEN BANYUMAS - Bagus Aditya; Agus Prabawa; Hari Winarto; Pandu Satrio Wibowo (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
Livestock is one of the agricultural sub-sectors that plays an important role in people’s lives, both in terms of economic and social values. Animal husbandry is the activity of growing animals and obtaining profits from these activities. Broiler chickens are the superior breeds resulting from crosses from chicken breeds that have high productivity, especially in producing chicken meat. The development of broiler chickens in Indonesia is quite good because it makes a real contribution to the community, namely in an effort to meet the needs of animal protein and also has a role in providing job opportunities. This study aims to analyze the effect of Business Lengt, Labor, Edocation, Age, Day Old Chick (DOC), Feed and Medicines on the income of broiler chicken farmers in Banyumas Regency. This study uses multiple linear regression data analysis. The results show that Business Length and Day Old Chick (DOC) had a significant positive effect on the income of broiler chicken farmers in Banyumas Regency. Labor, Education, age and Medicines has no significant effect on the income of broiler chicken farmers in Banyumas Regency. Meanwhile, Feed has a significant negative effect on the income of broiler chicken farmers in Banyumas Regency. This study implies to create skill and knowledge of chicken farmers for improving sustainable of farming. Keywords : Length of Business, Labor, Education, Age, Day Old Chick (DOC), Feed and Medicines.